Philosophical and Traditional Arts of Bugis-Makassar in Historical Perspective - Teng, Haji Muhammad Bahar Akkase (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: Traditional and modern, considered by many people, are two opposite things. In the context to the art, for example, many people assume that traditional art to be inferior to modern art, because modern art is considered more capable in terms of satisfying the soul or mind of society. This paper discusses the philosophy and history of traditional arts of Bugis-Makassar in South Sulawesi, Indonesia. Philosophy of art, that will be discussed, includes about ideas, meaning, experience, and intuition depicting symbolic meaning in the art of traditional of Bugis-Makassar. This paper uses literature review. Data were collected by conducting literature searches and documentation. Data has also been collected through the reading and study of literatures, and further to be discussed and analyzed to describe the philosophy and history of traditional arts of Bugis-Makassar descriptively. The results of the study showed that the art originated from pre-history and lasted until now. Art evolved into several types, namely primitive art, classic art, traditional art, modern art, and contemporary art. Traditional art is an element of art that are part of life in a specific clan, including Bugis-Makassar traditional arts which has had characteristic different from those in other areas. Traditional arts (Bugis) surviving until now include âPajaga Makkunraiâ dance and âSinriliâ (Makassar) are a form of art speech of the story, structured, rhythmic, and poetic chanted by the expert or called as âpasinriliâ.KEY WORD: Philosophy; Historical Perspective; Modern Art; Bugis-Makassar Traditional Arts; Survival.About the Author: Haji Muhammad Bahar Akkase Teng is a Senior Lecturer at the Department History, Faculty of Humanities UNHAS (Hasanuddin University) Makassar, Jalan Perintis Kemerdekaan Km.10 Makassar, South Sulawesi, Indonesia. The author is able to be contacted via mobile phone at: +628124246613 or via e-mail at: baharakkase@gmail.comHow to cite this article? Teng, Haji Muhammad Bahar Akkase. (2016). âPhilosophical and Traditional Arts of Bugis-Makassar in Historical Perspectiveâ in TAWARIKH: International Journal for Historical Studies, Vol.8(1) October, pp.69-78. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (January 22, 2016); Revised (May 20, 2016); and Published (October 28, 2016).